Stirring of Sea‐Ice Meltwater Enhances Submesoscale Fronts in the Southern Ocean. Issue 4 (26th March 2021) - Giddy, I.; Swart, S.; du Plessis, M.; Thompson, A. F.; Nicholson, S.‐A.
Abstract: In the sea‐ice‐impacted Southern Ocean, the spring sea‐ice melt and its impact on physical processes set the rate of surface water mass modification. These modified waters will eventually subduct near the polar front and enter the global overturning circulation. Submesoscale processes modulate the stratification of the mixed layer (ML) and ML properties. Sparse observations in polar regions mean that the role of submesoscale motions in the exchange of properties across the base of the ML is not well understood. The goal of this study is to determine the interplay between sea‐ice melt, surface boundary layer forcing, and submesoscale flows in setting properties of the surface ML in the Antarctic marginal ice zone. High‐resolution observations suggest that fine‐scale lateral fronts arise from either/both mesoscale and submesoscale stirring of sea‐ice meltwater anomalies. The strong salinity‐driven stratification at the base of the ML confines these fronts to the upper ocean, limiting submesoscale vertical fluxes across the ML base. This strong stratification prevents the local subduction of modified waters by submesoscale flows, suggesting that the subduction site that links to the global overturning circulation does not correspond with the location of sea‐ice melt. However, surface‐enhanced fronts increase the potential for Ekman‐driven cross‐frontal flow to modulate the stability of the ML and ML properties. The parameterization of submesoscale processes in coupled‐climate models, particularly those contributing to the Ekman buoyancy flux, may improve the representation of ML heat and freshwater transport in the ice‐impacted Southern Ocean during summer. Plain Language Summary: Sea‐ice melt around Antarctica is an annual event in which the state of the surface ocean is transformed, during which over 15 trillion liters of freshwater enter the upper ocean. This fresh layer separates the upper ocean from the deep ocean and suppresses the exchange of heat and gases—like carbon dioxide—between the deep ocean and the atmosphere, with important implications for the climate system. Using state‐of‐the‐art autonomous underwater gliders, we observed key physical properties of the surface ocean following the melt of sea‐ice. The presence of fine‐scale fronts (sharp changes in density), of less than 10 km at horizontal scales, revealed that sea‐ice melt not only stabilizes the upper ocean, but also provides additional energy for small eddies and filaments to form. While the eddies are unable to extend deeper than the fresher surface layer, they enhance the ocean response to winds. These findings may contribute to the improvement of global climate models and our understanding of how the ocean will react to changes in sea‐ice under a warmer climate. Key Points: Sea‐ice meltwater controls the buoyancy of the mixed layer during early summer Mixed layer eddies grow from mesoscale meltwater lateral gradients but are confined to the surface boundary layer Observations suggest that mixed layer variability at submesoscales is dominated by wind‐front interactions